EXISTENCE OF VENTURE CAPITAL: Alternative Financing Solutions Micro, Small & Medium Enterprises - Sulistyowati, Sulistyowati (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2015)
to contain the risk for investment through venture capital mechanism is not accompanied by a guarantee (collateral) so that prudence is needed by venture capital firms in selecting prospective venture is to be serve its business partners, in addition to a venture capital financing business is multidimensional ie as financial institutions (financial institution), Institute for equity investment company (corporate institution) and the Institute for entrepreneurs helper weak (humanistic institution). Venture capital in the financing of such financing has several characteristics aimed primarily at small companies or are new, but it has great potential to grow and has bright prospects, the field of technology or non-technology or business containing new breakthroughs which have difficulty in obtaining bank credit, pembiaayan who do venture capital temporary (generally long-term of 5 (five) to 10 (ten) years) to be divested its time, venture capital firms involved in corporate management pasanagn financed business, financing is not in the form of loans (loan) but inclusion capital (equity participation), given the high-risk financing for venture capital (risk capital) is not backed by collateral (collateral) so that the main motive is the finance business to profit (capital gain) is relatively high in return high risk financing, venture capital firms keuali which is funded from the government (public sector funds), PT Bahana. The parties involved in the venture capital financing Venture Capital Company (PMV) which is a party to provide financial assistance to companies that need funds. Couples who keduaPerusahaan Enterprises (PPU) as companies that need assistance to be able to expand its business dam that ketigaPihak Funders consisting of Bank Captive Fund, Investment Funds Captive Institution, Independent Funds, Public Sector Funds, International Funds, and funds from other sources, ie from other financial companies such sale of shares in the stock market, bonds, and other Iain, the four parties Accountant Publik.Adapun type of financing venture capital firm committed to his business partner companies there are three types namely Equity (Equity Participation), Obligasi Konversi (ConvertibleBond) and Sharing (profit and loss sharing)